Dermatological Manifestations of COVID-19: Data from a tertiary care hospital of Pakistan dedicated for COVID-19 Patients - Shawana Sharif , Muhammad Amer Saleem , Muhammad Umar ,Abdul Quddus Butt , Khizra Hashmi , Sumaira Abdullah, (Journal of Rawalpindi Medical College, 2021)
Background: Cutaneous manifestations of COVID-19 disease are poorly characterized around the globe. Data from Pakistan is lacking. Objective: To describe the cutaneous manifestations of COVID-19 disease in Pakistani population. Introduction: SARS-CoV-2 virus has rapidly spread reaching the level of a pandemic disease. COVID-19 can affect different organ systems including the skin. There is a wide variety of descriptions of the cutaneous manifestations of COVID-19. However, cutaneous manifestations of COVID-19 disease are poorly characterized around the globe. The data from Pakistan is especially lacking. Our study was aimed at describing the cutaneous manifestations of COVID-19 disease in Pakistani population. Materials and Methods: This cross sectional study was carried out at Benazir Bhutto Hospital from March 2020 till December 2020. A total of 150 patients were screened by senior dermatology postgraduate trainees who were deployed for the care of COVID-19 patients. The demographics, rash if any along with its complete history and description and laboratory investigations were noted on a preformed performa. The pictures of the rash were taken after verbal consent of patient or surrogate. The pictures were then discussed with the consultant for appropriate categorization. Results: A total of 150 patients with the diagnosis of COVID-19 were screened. The mean age of the subjects was 51.9 ± 17.2 years. There were 94 (62.7%) males and 56 (37.3%) females. The mean duration of illness at the time of screening was 12.5 ± 9.7 days. Only 7 (4.7%) COVID-19 patients showed skin lesions. These included generalized bullous pemphigoid like (1 patient), urticarial lesions (1 patient), vesicular eruption (1 patient), skin necrosis (1 patient) and maculopapular rash (3 patients). The average duration of illness at the time of dermatological manifestation of COVID-19 was 6.31 ± 2.3 days. Skin necrosis was associated with severe disease. Conclusion: The skin manifestations of COVID-19 patients in Pakistan are less as compared to reports and data from western world. However, they are in accordance with the data reported from few Asian countries. Regardless of this, the type, distribution and association of skin lesions with COVID-19 appear to be universal. This difference of frequency can be attributed to the racial differences or the variety of COVID-19 viral strains predominant in different countries. However, further studies are required to prove this association. Key Words: COVID-19, Dermatology, Skin Manifestations, Cutaneous Manifestations